Flight test validation of the dynamic model of a fuel cell system for ultra-light aircraft - Correa Perelmuter, Gabriel (2015)
The application of fuel cell technology to aircraft propulsion and/or energy supply is attracting a great deal of interest because of the undoubted advantages that can be attained in terms of pollution emissions and noise reduction. The goal of the ENFICA-FC project (Environmentally Friendly Inter City Aircraft powered by Fuel Cells) has been to develop and validate new fuel cell-based power system concepts for more/all electric aircrafts pertaining to the "inter-city" segment of the market. As a result of the project, a technology demonstrator has been designed, manufactured, and tested: a proton exchange membrane (PEM) fuel cell-based power system was installed in the Skyleader RAPID200 aircraft which underwent its demonstrative flights in 2010. On the basis of the flight experiences gained during the ENFICA-FC program, the main topic of this paper is the description and validation of the multi-disciplinary dynamic model of the PEMFC-based powertrain of the ultra-light aircraft, fed with a pure hydrogen flow. Within this paper, emphasis is given to the model validation and dynamic system behavior. In order to validate the predicted results, data from real fuel cell flight (two 40-minute missions performed during the ENFICA-FC test campaign) have been used and are presented in this paper.